2020
DOI: 10.1038/s41598-020-72149-6
|View full text |Cite
|
Sign up to set email alerts
|

Swine liquid manure: a hotspot of mobile genetic elements and antibiotic resistance genes

Abstract: The overuse or abuse of antibiotics as veterinary medicine and growth promoters accelerates antibiotic resistance, creating a serious threat to public health in the world. Swine liquid manure as an important reservoir of antibiotic resistance genes (ARGs) has received much attention, but little information is known regarding the occurrence, persistence and fate of ARGs-associated mobile genetic elements (MGEs) in swine farms, especially their change patterns and removal in full-scale piggery wastewater treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 78 publications
(86 reference statements)
2
12
0
Order By: Relevance
“…On the one hand, due to the extensive use of antibiotics in aquaculture (Cabello, 2006), ARGs can be transferred to from the skin, intestines and feces of dead farmed sh to water environment. On the other hand, it is reported that the spread of ARGs is closely associated with MGEs (Yang et al, 2020). And our results also showed that the ARGs' abundance was signi cantly related to MGEs.…”
Section: Water Resistomes Increase Due To Corpse Decomposition and Have Existed Persistentlysupporting
confidence: 67%
“…On the one hand, due to the extensive use of antibiotics in aquaculture (Cabello, 2006), ARGs can be transferred to from the skin, intestines and feces of dead farmed sh to water environment. On the other hand, it is reported that the spread of ARGs is closely associated with MGEs (Yang et al, 2020). And our results also showed that the ARGs' abundance was signi cantly related to MGEs.…”
Section: Water Resistomes Increase Due To Corpse Decomposition and Have Existed Persistentlysupporting
confidence: 67%
“…Furthermore, swine wastewater is an important source of antimicrobials in the environment, attributed to its large-scale application in the swine industry. Yang et al suggested a high prevalence of ARGs in piggery wastewater [81].…”
Section: Livestock Wastewatermentioning
confidence: 99%
“…Manure can be used as fertilizer, and depending on each country's regulations, wastewater can be released into the environment in various ways. However, it has been observed that pig manure and farm wastewater can contain antibiotic residues, antibiotic resistance genes and antibiotic resistant bacteria [72][73][74]. The quantity of these components is higher when the pigs are treated with antibiotics than when the pigs are not treated.…”
Section: From Pig To Environmentmentioning
confidence: 99%
“…Wastewater treatments achieved similar results [73]. Yang et al investigated two pig farm water treatment systems: one had an anaerobic tank and a ceramsite biofilter and the other had a plug flow anaerobic reactor, a temporary storage tank, a solid-liquid separation step, an upflow anaerobic sludge blanket, a primary clarifier tank, an anaerobic tank, an aerated tank and a second clarifier tank.…”
Section: From Pig To Environmentmentioning
confidence: 99%
See 1 more Smart Citation